Classical Guidance Service using Mind Mapping to Increase Stundents Time Management Skill - Agus Wibowo; Hadi Pranoto (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Time management skills are an important factor in supporting success. There are still many students who do not have time management skills. This research aims to improve students' time management skills using classical guidance services with Mind Mapping. The research location is SMAN 4 Metro City. The research sample consisted of 20 class XI students who were chosen randomly. Research data was collected using a time management skills scale. Data were analyzed using comparative statistical techniques. The results of the research show that there is a difference in the average value of time management skills before and after being treated with classical guidance services with the mediaMind Mapping. The results of the hypothesis test show that the significance value (2-tailed) is 0.000 <0.05. Thus, the hypothesis states that there are differences in time management skills before and after being given classical guidance services usingMind Mapping accepted. Based on the results of the hypothesis test, it can be concluded that classical guidance services use Mind Mapping effective for improving students' time management skills.